Lower-extremity ground reaction forces in collegiate baseball pitchers - Guido, J. A. Jr.; Werner, S. L. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to investigate ground reaction forces (GRF) in collegiate baseball pitchers and their relationship to pitching mechanics. Fourteen healthy collegiate baseball pitchers participated in this study. High-speed video and force plate data were collected for fastballs from each pitcher. The average ball speed was 35 ± 3 m/sec (78 ± 7 mph). Peak GRFs of 245 ± 20% body weight (BW) were generated in an anterior or braking direction to control descent. Horizontal GRFs tended to occur in a laterally directed fashion, reaching a peak of 45 ± 63% BW. The maximum vertical GRF averaged 202 ± 43% BW approximately 45 milliseconds after stride foot contact. A correlation between braking force and ball velocity was evident. Because of the downward inclination and rotation of the pitching motion, in addition to volume, shear forces may occur in the musculoskeletal tissues of the stride limb leading to many of the lower-extremity injuries seen in this athletic population.